Experimental investigations on the thermal performance of an ice storage system using twin concentric helical coil. (October 2020) - Abdelrahman, H.E.; Refaey, H.A.; Alotaibi, A.; Abdel-Aziz, Ali A.; Abd Rabbo, M.F.
Highlights: Cool thermal energy storage (CTES) offers a big advantage for peak shift. Thermal performance of ice storage system using a novel twin concentric helical coil. Effect of flow rate seems to be less effective compared to the inlet temperature during charging and discharging processes. Shut down the chiller early as possible for the last 26–41% of the complete charging time to save power. No performance advantage to fully discharge the storage tank after 74–79% of the complete discharging time. Abstract: The cool thermal energy storage (CTES) offers a big advantage for peak shift of high electrical power consumed by air conditioning systems. An experimental analysis for studying the thermal performance of ice storage system with twin concentric helical coil (TCHC) is conducted in the present work. Effects of operating conditions such as the heat transfer fluid (HTF) inlet temperature and flow rate on the solidified/melted mass fraction, percentage energy stored/regained, and average charging/discharging rate during charging and discharging processes are investigated. An experimental setup composed of TCHC immersed in distilled water as a phase change material (PCM) in an insulated tank is used in the present study. Three different HTF inlet temperatures of (−8, −10, and −12 °C) and (10, 12, and 14 °C) for charging and discharging processes, respectively and HTF volume flow rates (5.0, 7.5, and 10 l/min) are investigated. The results show that, about 90% of the energy stored is achieved at 59–74% of the complete charging time according to the tested parameter range in the current study. Moreover, the HTF volume flow rates have a relatively small effect on the percentage energy stored and seems to be less effective compared to the inlet HTF temperature during charging process.